Strategic Impact through International Sourcing : Used Car Retailers in Finland - Vahala, Juho (My University, 2021)
The number of used passenger cars imported to Finland has grown steadily in the past few years. Not only private persons, but also car dealerships import vehicles from abroad and sell them in Finland. There has also been a lot of public discussion and news articles about importing used cars, which makes it an important topic. The objective of this study was to find out why the Finnish car dealers import used cars to Finland. To meet this objective, the study aimed to find out the drivers and constraints related to international purchasing. The study was conducted as a qualitative research and the data was collected by interviewing professionals from four different Finnish car dealerships, that are engaged in international sourcing. The study found that the main driving forces for the imports were the lack of domestic supply and pricing. The constraints that impacted the imports were problems with logistics and quality. The costs were also a constraint worth considering, as they were sometimes hard to estimate. The largest costs for the car dealerships apart the vehicle and the taxes were costs related to logistics. The results suggest that there were various reasons for importing used cars from the dealers’ perspective. The main forms of strategic impact they were pursuing were widening the supply, keeping products that sell at stock and boosting their performance by creating more sales. Based on the key findings, managerial implications were made. These recommendations included analyzing the pursued strategic impact carefully before starting the operations and noting that the pursued impact might not be reached in a short amount of time. To overcome the challenges of the international purchasing, it is recommended to invest time and effort to finding a suitable logistics partner and network to source the cars from. Finally, the researcher also made some suggestions for further research on the topic, which included making a longitudinal study and studying companies that have reached a higher level in their international operations.

Käytettynä Suomeen tuotujen autojen lukumäärä on kasvanut tasaisesti viime vuosien aikana. Tuonti ei tapahdu pelkästään yksityisten ihmisten toimesta, vaan myös autoliikkeet tuovat autoja ulkomailta myytäväksi Suomeen. Aiheesta on keskusteltu laajasti julkisuudessa ja se on ollut esillä lehdissä, joka lisää aiheen kiinnostavuutta. Tämän tutkimuksen tavoitteena oli selvittää miksi suomalaiset autoliikkeet tuovat käytettyjä autoja Suomeen. Tämän tavoitteen saavuttamiseksi, tutkimuksessa selvitettiin mitkä asiat vaikuttavat kansainväliseen ostotoimintaan ajureina ja rajoitteina. Tutkimus toteutettiin laadullisena tutkimuksena ja data kerättiin haastattelemalla autoalan ammattilaisia neljästä eri suomalaisesta autoliikkeestä, jotka tuovat autoja Suomeen. Tutkimuksessa selvisi, että tärkeimmät kansainvälisen oston ajurit liittyivät kotimaisten markkinoiden puutteeseen tarjonnassa ja hinnoitteluun. Rajoitteet, jotka vaikuttivat tuontipäätökseen, ilmenivät ongelmina logistiikan ja laadun suhteen. Kulut olivat myös huomioitava rajoite, sillä niiden ennustaminen oli ajoittain hankalaa. Suurimmat kulut maahantuoville liikkeille itse ajoneuvon ja verojen lisäksi aiheutuivat logistiikan kustannuksista. Tuloksista selvisi, että käytettyjen autojen tuontiin oli monia syitä liikkeiden näkökulmasta. Tuonnilla tavoiteltiin strategista vaikutusta valikoiman laajentamisen, myyvien tuotteiden varastossa pitämisen ja kasvaneen myynnin tuoman suorituskyvyn kautta. Tulosten pohjalta tehtiin myös käytännön suosituksia. Suosituksia olivat tavoitellun strategisen vaikutuksen analysointi tarkasti ennen tuonnin aloittamista, ottaen huomioon, että tavoiteltu vaikutus ei välttämättä ole saavutettavissa lyhyellä aikavälillä. Kansainvälisen ostotoiminnan haasteiden voittamiseksi suositeltiin käyttämään aikaa ja panostamaan sopivan logistiikkakumppanin löytymiseen ja autojen ostopaikkojen verkoston kehittämiseen ulkomailla. Lopuksi tutkija antoi myös ehdotuksia aiheen jatkotutkimusta koskien. Mahdollisia jatkotutkimusaiheita olivat pitkittäistutkimus tuontia harjoittavista kauppiaista ja tutkimus koskien yrityksiä, joiden maahantuonti on korkeammalla tasolla, kuin tässä tutkimuksessa esiintyvillä yrityksillä.
Keywords: Imports, car market, used cars, car dealers, international purchasing